The survival benefits of adjuvant radiotherapy for malignant meningioma: a retrospective cohort study (Universa Medicina, 2025)
BackgroundMalignant meningiomas (MM) are rare aggressive tumors associated with poor survival outcomes. Due to their rarity, there is limited data on the outcomes and prognostic factors of MM patients, particularly on adjuvant radiotherapy roles in this tumor population. This study aims to investigate the clinical characteristics, prognostic factors, and survival outcomes of MM with focus on survival benefits of adjuvant radiotherapy.MethodsThis retrospective cohort study analyzed 19 MM patients, who were initially subjected to postoperative radiotherapy, at Dr. Kariadi General Hospital, Semarang, from 2013 to 2023. Kaplan-Meier analysis was used to estimate survival rates at 1, 2, and 5 years. Univariate and multivariate Cox regression analyses were performed to identify factors associated with overall survival (OS). Variables with a p-value ≤ 0.25 in univariate analysis were included in the multivariate models.ResultsThe median OS was 16 months (95% CI 0.0–40.2), with estimated 1-year, 2-year, and 5-year survival rates of 52.6%, 42.1%, and 15.8%, respectively. Adjuvant radiotherapy (RDT) was associated with a significantly improved OS (p